Architecture as an Instrument of Colonial Power - Schellhorn, Adrian (Institute for Research and Community Services Udayana University, 2025)
Colonial architecture and urban planning have historically served as potent tools for asserting dominance and enforcing social hierarchies within colonized regions. This paper examines the multifaceted role of architecture in colonial power structures, focusing on its applications in urban planning and design during the French colonial era, with insights applicable to broader colonial contexts. Drawing on theoretical frameworks from postcolonial studies, this study explores how urban spaces were strategically designed to reinforce segregation, alienate indigenous populations, and symbolize colonial authority. The research method involves a critical analysis of case studies from Algiers and Hanoi, as well as a review of key texts including Gwendolyn Wright’s The Politics of Design in French Colonial Urbanism and Davide Ponzini’s Transnational Architecture and Urbanism. These sources illuminate how colonial administrators adapted European planning models and integrated transnational architectural influences to craft spaces of both dominance and cultural negotiation. Findings reveal that while colonial architecture functioned as a mechanism of control, indigenous communities subverted its intent through cultural adaptations and repurposing of spaces. Additionally, the hybridization of colonial and local architectural styles highlights the complexities of power, negotiation, and resilience in colonized urban landscapes. This study underscores the enduring impact of colonial urban planning on contemporary cities, where spatial inequalities and inherited architectural forms persist. It advocates for postcolonial urban planning approaches that prioritize inclusivity and cultural representation, transforming colonial legacies into equitable urban environments. These insights hold significant implications for architects, urban planners, and policymakers seeking to reconcile historical imbalances and foster socially cohesive communities.